A comprehensive assessment of non-indigenous species requires the combination of multi-marker eDNA metabarcoding with classical taxonomic identification - Stefano Varrella; Silvia Livi; Cinzia Corinaldesi; Luca Castriota; Teresa Maggio; Pietro Vivona; Massimo Pindo; Sebastiano Fava; Roberto Danovaro; Antonio Dell’Anno (Environment International)
In marine environment, non-indigenous species (NIS) can alter natural habitats and cause biodiversity loss with important consequences for ecosystems and socio-economic activities. With more than 1000 NIS introduced over the last century, the Mediterranean Sea is one of the most threatened regions worldwide, requiring an early identification of newly entered alien species for a proper environmental management. Here, we carried out environmental-DNA (eDNA) metabarcoding analyses, using multiple molecular markers (i.e., 18S rRNA, COI, and rbcL) and different genetic databases (i.e., NCBI, PR2, SILVA, MIDORI2, MGZDB, and BOLD), on seawater and sediment samples collected on a seasonal basis in three Mediterranean ports located in the North Adriatic, Ionian and Tyrrhenian Sea to identify marine species, and particularly NIS. The use of the multi-marker eDNA metabarcoding allowed the identification of a higher number of species compared to the morphological analyses (1484 vs. 752 species), with a minor portion of species shared by both approaches. Overall, only 4 NIS were consistently identified by both morphological and molecular approaches, whereas 27 and 17 NIS were exclusively detected by using eDNA metabarcoding and classical taxonomic analyses, respectively. The eDNA metabarcoding allowed also identifying the genetic signatures of 5 NIS never reported in the Italian waters. We conclude that eDNA metabarcoding can represent a highly sensitive tool for the early identification of NIS, but a comprehensive census of the NIS requires the combination of molecular and morphological approaches.